Poster 162: Glenoid Bone Loss Directly Affects Hill-Sachs Morphology: An Advanced 3-Dimensional Analysis. Issue 7 (30th July 2022) - Golijanin, Petar; Peebles, Annalise; Douglass, Brenton; Arner, Justin; Provencher, Matthew; Peebles, Liam
Objectives: The purpose of this study was to 1.) qualitatively and quantitatively analyze the interplay between glenoid bone loss (GBL) and Hill-Sachs lesions (HSL) in a cohort of anterior instability patients using 3-dimensional (3-D) imaging software and 2.) assess the relationships between GBL and HSL characteristics. Methods: Patients with anterior shoulder instability with a minimum of 5% GBL with evidence of HSL confirmed on computed tomography were identified. 3-D models of the unilateral proximal humeral head and en face sagittal oblique view of the glenoid were reconstructed using Mimics (Materialise NV, Leuven, Belgium) software. GBL as well as surface area (SA), width, defect length, and glenoid track width was quantified. The volume, SA, width, and depth of identified HSLs were quantified along with their location (medial, superior, and inferior extent) on the humeral head. The severity of glenoid bone loss was categorized by low grade (0-10%), moderate grade (>10% to 20%), high grade (>20% to 30%), and extensive (>30%). Analysis of variance was then computed to determine significance (p < 0.05) between severity of GBL and associated HSL parameters. Results: 100 patients met inclusion criteria (mean age: 27.9 years, range: 18 to 43 years), which included 58 right shoulders and 42 left shoulders (84 male, 16 female). Among groups, 32 patients presented with low grade GBL (μ GBL = 6.1%), 38 patients with moderate grade (μ GBL = 16.2%), 17 with high grade ( μ GBL = 23.7%), and 13 with extensive GBL (μ GBL = 34.0%), with an overall mean GBL of 18.1% (range 5% - 39%). Patients with 0-10% GBL had significantly narrower (average and max width) ( p < 0.03) and deeper (average depth) (p = 0.002) HSLs compared with all other GBL groups, while greater GBL was associated with wider and shallower HSLs. GBL width, percent width loss, defect length, and glenoid track width all significantly differed across the four GBL groups (p < 0.05). Conclusions: Hill-Sachs Lesions (HSLs) have different morphological characteristics depending on the amount of glenoid bone loss (GBL). GBL is directly related to the characteristics of HSLs. Smaller glenoid defect size is associated with narrower and deeper HSLs. Management of the humeral head and glenoid must be appropriately tailored given the distinct interplay between GBL severity and HSL.